Android application development for dummies - Burton, Michael; Felker, Donn (Wiley, 2012)
This is your easy-to-use guide to creating applications on the Android platform The Android OS continues to expand offering app developers access to one of the largest platforms available, and this straightforward guide walks you step-by-step through the process of creating amazing Android applications. In this second edition of his bestselling book, Android programming expert Donn Felker explains how to download the SDK, get Eclipse up and running, code Android applications, and submit your finished products to the Android Market. Featuring two sample programs, this introductory book explore.
Print version record
Keywords: Android (Electronic resource); Application software -- Development; Mobile computing; Logiciels d'application; Développement; Informatique mobile; COMPUTERS; Programming; Open Source; COMPUTERS; Software Development & Engineering; Tools; COMPUTERS; Software Development & Engineering; General; Application software; Development; App; Programm; Mobile Computing; Android; Systemplattform